Formation and Development of Professional Competence of a Teacher in the Development of Basic Technologies - Mamirov Khairullo Khamzaevich (International Journal on Orange Technologies, 2022)
The adoption of the” Law on Education" of the Republic of Uzbekistan in a new edition sets new goals for teachers, the implementation of which provides for a harmoniously developed, creative, able to solve the tasks of the student's personality. Achieving these and other results is impossible without using modern technologies in their professional activities. The article highlights some of the basic competencies.